The evolution of the terrestrial‐terminating Irish Sea glacier during the last glaciation. (7th July 2020) - Chiverrell, Richard Christopher; Thomas, Geoff Stephen Powell; Burke, Matthew; Medialdea, Alicia; Smedley, Rachel; Bateman, Mark; Clark, Chris; Duller, Geoffrey A. T.; Fabel, Derek; Jenkins, Geraint; Ou, Xianjiao; Roberts, Helen Marie; et al.
ABSTRACT: Here we reconstruct the last advance to maximum limits and retreat of the Irish Sea Glacier (ISG), the only land‐terminating ice lobe of the western British Irish Ice Sheet. A series of reverse bedrock slopes rendered proglacial lakes endemic, forming time‐transgressive moraine‐ and bedrock‐dammed basins that evolved with ice marginal retreat. Combining, for the first time on glacial sediments, optically stimulated luminescence (OSL) bleaching profiles for cobbles with single grain and small aliquot OSL measurements on sands, has produced a coherent chronology from these heterogeneously bleached samples. This chronology constrains what is globally an early build‐up of ice during late Marine Isotope Stage 3 and Greenland Stadial (GS) 5, with ice margins reaching south Lancashire by 30 ± 1.2 ka, followed by a 120‐km advance at 28.3 ± 1.4 ka reaching its 26.5 ± 1.1 ka maximum extent during GS‐3. Early retreat during GS‐3 reflects piracy of ice sources shared with the Irish‐Sea Ice Stream (ISIS), starving the ISG. With ISG retreat, an opportunistic readvance of Welsh ice during GS‐2 rode over the ISG moraines occupying the space vacated, with ice margins oscillating within a substantial glacial over‐deepening. Our geomorphological chronosequence shows a glacial system forced by climate but mediated by piracy of ice sources shared with the ISIS, changing flow regimes and fronting environments.